1998
DOI: 10.1016/s0304-3959(97)00142-5
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of factors affecting the ratios of morphine and its major metabolites

Abstract: In a systematic review of 57 studies with information on 1232 patients we examined the effect of age, renal impairment, route of administration, and method of analysis on the ratios of morphine-3-glucuronide:morphine (M3G:M) and morphine-6-glucuronide:morphine (M6G:M) and the relative concentrations of M3G and M6G. Across all studies the range of the ratios of metabolites to morphine was wide (0.001-504 for M3G:M, and 0-97 for M6G:M). Neonates produced morphine glucuronides at a lower rate than older children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(94 citation statements)
references
References 21 publications
9
85
0
Order By: Relevance
“…The ratio of morphine to M6G concentrations ranged from 1 : 5.5 to 1 : 6.7, which is in agreement with previous studies (15,16).The high number of patients with undetectable plasma morphine concentrations prior to the morning drug dosing is probably due to the low daily CR opioid dose in these patients (mean daily morphine dose 75 mg) since three of these patients had very low oxycodone concentrations, too. In previous clinical studies of cancer patients, it has been found that even low daily doses of CR morphine have resulted in measurable plasma morphine concentrations (17,18) but the assay limit for morphine has been lower (1 ng:ml) (19) than in the present study (5 ng:ml).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The ratio of morphine to M6G concentrations ranged from 1 : 5.5 to 1 : 6.7, which is in agreement with previous studies (15,16).The high number of patients with undetectable plasma morphine concentrations prior to the morning drug dosing is probably due to the low daily CR opioid dose in these patients (mean daily morphine dose 75 mg) since three of these patients had very low oxycodone concentrations, too. In previous clinical studies of cancer patients, it has been found that even low daily doses of CR morphine have resulted in measurable plasma morphine concentrations (17,18) but the assay limit for morphine has been lower (1 ng:ml) (19) than in the present study (5 ng:ml).…”
Section: Discussionsupporting
confidence: 91%
“…In cancer patients, no simple correlation between opioid and metabolite concentrations and pain relief has been found (19), although Faura et al (16) have reported a tendency towards greater stable phase morphine concentrations in cancer patients with optimal pain control.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is the major organ involved in the glucuronidation of morphine [31]. Morphine-3-gluronide (M3G) is the major metabolite (M6G/ M3G ratio approximately 0.15) [35]. Morphine-glucuronides are hydrophylic compounds, that are mainly excreted in urine, and in minor quantities in bile.…”
Section: Resultsmentioning
confidence: 99%
“…These studies have consistently demonstrated elevated metabolite levels 88,89,92,[101][102][103][104][105][106] when measured in renal impairment. They also have suggested a frequent association between renal impairment and opioid toxicity.…”
Section: Pathophysiology Of Opioid-associated Cognitive Dysfunctionmentioning
confidence: 91%